Efficient surface passivation of black silicon using spatial atomic layer deposition. (September 2017) - Heikkinen, Ismo T.S.; Repo, Päivikki; Vähänissi, Ville; Pasanen, Toni; Malinen, Ville; Savin, Hele
Abstract: Nanostructured silicon surface (black silicon, b-Si) has a great potential in photovoltaic applications, but the large surface area requires efficient passivation. It is well known that b-Si can be efficiently passivated using conformal Atomic Layer Deposited (ALD) Al2 O3, but ALD suffers from a low deposition rate. Spatial ALD (SALD) could be a solution as it provides a high deposition rate combined with conformal coating. Here we compare the passivation of b-Si realized with prototype SALD tool Beneq SCS 1000 and temporal ALD. Additionally, we study the effect of post-annealing conditions on the passivation of SALD coated samples. The experiments show that SALD passivates b-Si surfaces well as charge carrier lifetimes up to 1.25 ms are obtained, which corresponds to a surface recombination velocity S eff, max of 10 cm/s. These were comparable with the results obtained with temporal ALD on the same wafers (0.94 ms, S eff, max 14 cm/s). This study thus demonstrates high-quality passivation of b-Si with industrially viable deposition rates.